CCL28 Downregulation Attenuates Pancreatic Cancer Progression Through Tumor Cell-Intrinsic and -Extrinsic Mechanisms. (December 2021) - Yan, Jingjing; Yuan, Pengkun; Gui, Liming; Wang, Zhixue; Yin, Pan; Gao, Wei-Qiang; Ma, Bin
C-C motif chemokine ligand 28 (CCL28) has been reported to be pro-tumoral in several cancer types. However, the role of CCL28 in pancreatic ductal adenocarcinoma (PDAC) progression remains unclear. CCL28 mRNA expression in tumors from PDAC patients was found to be elevated as compared to normal pancreas. CCL28 expression was also negatively correlated with overall survival (OS) in pancreatic cancer patients. Our in vitro experiments showed that CCL28 knockdown impairs the proliferation of mouse pancreatic cancer cell line PAN02. Moreover, in both immunocompetent syngeneic mice and immunodeficient NOD-SCID mice, CCL28 deficiency significantly attenuated the growth of subcutaneous PAN02 tumors. In syngeneic mouse model, CCL28 downregulation remodeled the pancreatic tumor microenvironment by suppressing the infiltration of both regulatory T (Treg) cells, myeloid-derived suppressor cells, and activated pancreatic stellate cells, and upregulating the expression of lymphocyte cytotoxic proteins including perforin and granzyme B. In conclusion, our work demonstrates that CCL28 is a potential target for pancreatic cancer treatment and CCL28 blockade could inhibit tumor growth through both tumor-cell-intrinsic and extrinsic mechanisms.